Odpowiedź :
Odpowiedź:
[tex]\frac{y-5}{3}[/tex] = [tex]\frac{y}{5}[/tex]
5y - 25 = 3y
2y = 25
y= 25/2
8x -3 = 9 + 4x
4x = 12
x =3
4(x+3) + 5 = 3 - 3x
4x + 12 + 5 = 3 - 3x
7x = 3 - 17
x = -2
[tex]\frac{-2}{x}[/tex] = [tex]\frac{5}{8}[/tex]
5x = -16
x = -16/5
Odpowiedź:
y- 5/3= y/5
5 ( y-5) = 3*y
5y - 25 =3y
5y-3y= 25
2y= 25 /:2
y= 25/2= 12 i 1/2
spr... ( 12i 1/2 -5 ):3 = 12 i 1/2 :5
7 i 1/2 :3= 25/2 :5
15/2*1/3= 25/2 *1/5 ( skracamy 15 i 3 przez3, oraz 25 i 5 przez 5)
5/2= 5/2
L=P
zad.
4 ( x+3) +5 = 3 - 3x
4x +12 +5= 3-3x
4x+3x = 3 -5-12
7x= -14 /:7
x= -2
spr... 4* (-2) +12 +5= 3- 3*(-2)
-8 +12 +5= 3 +6
9= 9
L=P
zad.
-2/x = 5/8
5*x= -2*8
5x = -16 /:5
x= -16/5 = - 3 i 1/5
spr... -2 : ( -16/5)= 5/8
-2* (-5/16)= 5/8 ( skracamy 2 i 16 przez 2)
-1 *(-5/8) = 5/8
5/8= 5/8
L=P
Szczegółowe wyjaśnienie: